2006
DOI: 10.1007/s12030-006-0007-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of the biocompatibility of chemically modified GaAs surfaces

Abstract: GaAs has excellent optical, electrical, and mechanical properties and shows promise to be used in the fabrication of novel devices. However, the unprotected GaAs surface can release heavy metal compounds such as AsO x, which are toxic to living cells. A promising approach to reduce or eliminate this release relies on the passivation of the GaAs surface using different chemical approaches. In this work, we compared three different passivation methods aimed at enhancing the viability of cells on GaAs. Protective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The PAH/PSS polyelectrolyte coatings were cytotoxic while the peptide coating (at a relatively high concentration) was not toxic. 41…”
Section: Planar Semiconductorsmentioning
confidence: 99%
“…The PAH/PSS polyelectrolyte coatings were cytotoxic while the peptide coating (at a relatively high concentration) was not toxic. 41…”
Section: Planar Semiconductorsmentioning
confidence: 99%
“…The substrate is generally an alloy of GaAs with a refractive index close to that of the waveguide core, so that thick films are needed, resulting in expensive and time-consuming fabrication, and weaker evanescent interaction. Moreover, GaAs is not biocompatible and can release toxic substances such as As or AsO x into aqueous analytes which can, for example, lead to cell death. , …”
Section: The State Of the Art Of Thin-film Mir Waveguidesmentioning
confidence: 99%
“…Moreover, GaAs is not biocompatible and can release toxic substances such as As or AsO x into aqueous analytes which can, for example, lead to cell death. 37,38 Chalcogenides. Planar waveguides of mercury cadmium telluride (MCT) were fabricated as on-chip MIR transducers and evanescent field sensing of acetone was demonstrated by depositing a drop of solution on the waveguide.…”
Section: Waveguidesmentioning
confidence: 99%
“…It was shown that GaAs surfaces can be coated with various biocompatible materials to prevent the release of toxic substances. 64 A potential coating material is Parylene C (poly-paraxylylene), which has been widely used as a structural material for bioMEMS systems, and as a coating material in electronic circuits and implantable electrodes. 65 Parylene C has several desirable properties, such as biocompatibility, chemical inertness, high flexibility, and reliable hermetic sealing of the electronic implantable systems.…”
Section: Floating Light-activated Microelectrical (Flame) Stimulatormentioning
confidence: 99%